Psychosocial care from the perspective of nurses working in oncology: A qualitative study. (June 2018) - Güner, Perihan; Hiçdurmaz, Duygu; Kocaman Yıldırım, Nazmiye; İnci, Figen
Abstract: Purpose: In cancer patients, unmet psychosocial needs are a common occurrence. The purpose of this study was to determine the views, obstacles, and needs of the nurses working with adult oncology patients with regards to psychosocial care. Methods: A qualitative descriptive research design conducted through focus group interviews was adopted for the study. Thirty nurses providing care for cancer patients in adult oncology departments of three hospitals in Turkey with comprehensive oncology centers were involved in the interviews. The interviews were conducted via a semi-structured interview form. In analyzing the data, content analysis technique was utilized. Results: In the study, three main themes and seven sub-themes were determined. These were as follows: "Challenge" ( Sub-themes: The nature of the disease: A thin line between life and death; Lack of team/institutional support; Lack of time, staff, and knowledge; Vulnerability of the patient and their family ), "reward and cost" ( Sub-themes: Satisfaction; Personal growth; Exhaustion ), and "essential but hard to define". Conclusions: This study reveal that nurses have difficulty delivering psychosocial care, which they perceive in abstract terms, in an environment where the disease is still considered fatal, the conditions of the patients change constantly, and they cannot receive the necessary support. It can be important that, as well as supportive institutional regulations, the nurses are in need of necessary assistance to help them change their own perceptions on cancer, to become emotionally stronger, and to acquire necessary knowledge and skills to give psychosocial care. Highlights: The nurses viewed cancer as fatal but they were aware of the personal and professional rewards of working in oncology. The nurses had difficulties defining and setting the frame of psychosocial care, and propriety of their approach. The nurses believed that other staff members also needed to take an active part in psychosocial care.